Effectiveness of Self-Made E-Learning Videos for Dual Sports in Enhancing The Performance of Bachelor of Physical Education Students - Johncel P Bueza; Timothy John O Vallejo; Hanz Martin Flores; Maria Teresa M Rodriguez (Research Synergy Foundation, 2023)
This study aimed to determine the effectiveness of self-made e-learning videos in enhancing the dual sport footwork performance of Bachelor of Physical Education students at Laguna State Polytechnic University. This study employed a pre-experimental – single-group pretest, post-test research design. The participants were purposively selected and are taking dual sports courses. Their performances were evaluated by determining the pretest and posttest mean scores and the significant differences of the variables and describing the learners' satisfaction rate on the effectiveness of e-learning videos. Based on the findings, there was a significant difference in the participants' pretest and posttest mean scores, which means that using e-video in PE sports courses enhanced their performance. The e-learning videos influence students' understanding of the basic footwork for dual sports and with high satisfaction with the learnings acquired from the videos. It was concluded that Self-made e-learning videos are effective, efficient, and useful alternative learning material for teaching dual sport footwork. It is encouraged that e-videos for dual sports courses could be adopted across the BPED LSPU system, and the use of e-learning videos may replicate in other education courses in other universities. In addition, there is a need to develop strategies to enhance the effectiveness of the e-learning course.